2017
DOI: 10.1039/c7ra02765f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antibacterial evaluation of nanofibrillated cellulose grafted by a novel quinolinium silane salt

Abstract: Nanofibrillated cellulose (NFC) is a bio-based nanomaterial with no intrinsic antibacterial properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The patterns (Figure a) illustrate that the cross-linking reaction maintained the original crystalline structure and that the CrI varied significantly from 63.7% to 34.8% with increasing MTMS. A possible reason for this is that the grafted polysilane molecules broke the inter- and intramolecular hydrogen bonds of TCNF fibrils, which resulted in the opening of hydrogen-bonded cellulose chains and new amorphous region to be formed. …”
Section: Resultsmentioning
confidence: 99%
“…The patterns (Figure a) illustrate that the cross-linking reaction maintained the original crystalline structure and that the CrI varied significantly from 63.7% to 34.8% with increasing MTMS. A possible reason for this is that the grafted polysilane molecules broke the inter- and intramolecular hydrogen bonds of TCNF fibrils, which resulted in the opening of hydrogen-bonded cellulose chains and new amorphous region to be formed. …”
Section: Resultsmentioning
confidence: 99%
“…The MCC treated with higher content of APTES showed a slightly higher nitrogen content, being the highest for MCC-Si (1:5). According to Hassanpour et al (2017), higher N content can be related to a successful grafting of the aminosilane onto the cellulose surface. Saini, Belgacem, Salon, & Bras, (2016) also found that the initial silane concentration signi cantly affected the grafting e ciency.…”
Section: Amount Of Aptes Grafted Onto MCC Surfacementioning
confidence: 99%
“…These superficial molecular features remain the grandest challenge to overcome during modification to enhance processability and performance. 19 Moreover, at higher fibrillation, the amorphous-to-crystalline ratio of its structure increases 20 and a greater number of surface hydroxyl groups become available due to higher exfoliation of fibrils. These fibrils tend to form hydrogen bonds with the ubiquitous water molecules resident in the system whereas the greater levels of amorphous regions permit more water molecules to enter the inter-and intrafibrillar spaces.…”
Section: ■ Introductionmentioning
confidence: 99%